Peran Kreativitas dalam Penggunaan Media Alat Peraga dan Teknik Berhomili di Stasi Santo Bonaventura Situnggaling, Paroki Santo Fransiskus Asisi Saribudolok - Thomas N. Tarigan; Paulinus Tibo; Gurning, Livo Novita Gurnin; Ona Sastri Lumban Tobing (Perkumpulan Perguruan Tinggi Agama Katolik Indonesia, 2024)
The creativity of church administrators in homily in Stasi Santo Bonaventura Situnggaling Paroki Santo Fransiskus Asisi Saribudolog became the orientation or concern in this research because the Medan Archdiocese Church tried to educate the laity through pastoral functionaries taking an active part, especially in leading the celebration of the word on Sundays without faith and giving homilies. This approach uses three techniques, including interviews with informants directly with listening techniques, data collection through observation, and supporting documents as part of the documentation. The stages of data analysis began with data reduction, displaying data, and testing the truth of the data by triangulating techniques and sources. Efforts made with this approach found two essential aspects of the creativity of Church administrators in domicile, which are used as findings: (1) Church administrators have creativity in presenting homilies, especially the use of props, although not yet optimal, body language: facial expressions, body gestures, voice intonation and dialogue contact with the congregation. (2) Homilies bear fruit for the faithful in this parish, such as churchgoers who experience a deep understanding of the meaning of the word of God for life, experience the presence of God in life now, and change life in true repentance. People feel prosperity in life. However, many people in this Stasi still have not been able to make homilies good fruitsin their daily lives.